Strategy of Human Resource Development in the Shipping and Logistics Sector to Face Industrial Era 4.0 - Nugroho, Dony Ari (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The Industry 4.0 era, driven by Artificial Intelligence (AI), the Internet of Things (IoT), automation, and big data analytics, has significantly transformed the shipping and logistics sector. While digitalization improves efficiency, it also presents challenges in workforce adaptation. According to a 2023 World Economic Forum report, 50% of employees will require reskilling by 2025, yet only 30% of logistics companies have fully embraced digital workforce transformation strategies. This research analyzes human resource (HR) development strategies to equip workers with skills aligned with Industry 4.0 demands. This study uses a qualitative approach, utilizing peer-reviewed journals, industry reports, and government publications. Data analysis follows Miles and Huberman's interactive model, consisting of data reduction, data presentation, and conclusion drawing, ensuring structured and comprehensive insights. Findings indicate that HR development strategies in the shipping and logistics sector require three key approaches: (1) Enhancing digital competencies through technology training and online learning platforms; (2) Developing adaptive skills, such as problem-solving, critical thinking, and agility, to navigate technological shifts; and (3) Implementing HR technology for recruitment, training, and performance management. Additionally, collaboration with industries and policymakers is essential to accelerate workforce digital transformation. By applying these strategies, the shipping and logistics sector can build a competent, agile workforce, ensuring long-term sustainability and competitiveness in the Industry 4.0 landscape.